2022
DOI: 10.1007/s00520-022-07089-0
|View full text |Cite
|
Sign up to set email alerts
|

Family caregiver ambassador support for caregivers of patients with newly diagnosed hematological cancer: a feasibility study

Abstract: Purpose This study investigated the feasibility of a one-on-one peer support intervention in family caregivers of newly diagnosed patients with a hematological cancer during initial treatment. Methods The study was a one-arm feasibility study including family caregivers of newly diagnosed patients with hematological cancer ( n = 26) and caregiver ambassadors who were family caregivers of previously treated patients as peer supporters ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…The loneliness and confusion experienced by some family members in our study suggests that peer support would be useful. A recent feasibility study found one-to-one peer support was acceptable and beneficial for caregivers of those with newly diagnosed haematological cancers, 57 with similar findings for groupbased support. 58 This study has allowed us to capture a breadth of experiences and changing attitudes by interviewing patients at varying intervals post diagnosis, and with different treatment pathways.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The loneliness and confusion experienced by some family members in our study suggests that peer support would be useful. A recent feasibility study found one-to-one peer support was acceptable and beneficial for caregivers of those with newly diagnosed haematological cancers, 57 with similar findings for groupbased support. 58 This study has allowed us to capture a breadth of experiences and changing attitudes by interviewing patients at varying intervals post diagnosis, and with different treatment pathways.…”
Section: Discussionmentioning
confidence: 63%
“…The loneliness and confusion experienced by some family members in our study suggests that peer support would be useful. A recent feasibility study found one-to-one peer support was acceptable and beneficial for caregivers of those with newly diagnosed haematological cancers,57 with similar findings for group-based support 58…”
Section: Discussionmentioning
confidence: 76%